Dampak Perubahan Iklim terhadap Virus Timun dan Pengelolaannya - Dorthi Ester Junita Daeli; Intan Novibriani Zendrato; Fidar Kristiana Zai (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
The agriculture sector is facing unprecedented challenges as a result of climate change. As temperatures continue to rise and weather patterns change, the dynamics of plant-virus interactions change significantly, requiring innovative solutions to ensure global food security. This review article examines the relationship between climate change and the prevalence and severity of cucumber virus diseases, their impact on cucumber yield and quality, and subsequent economic implications, with a focus on the critical pathogen cucumber mosaic virus (CMV). The method in this journal article uses library research, which is a method with data collection by understanding and studying theories from various literatures related to the research. The results showed that as climate change increases, it is imperative to investigate its impact on cucumber virus management, specifically how increasing temperatures and changing rainfall patterns may affect virus epidemiology and disease resistance mechanisms. In addition, exploring integrated pest management strategies that combine traditional breeding with modern biotechnology advances is essential. The application of RNA-based technologies presents a promising avenue for effective virus control, potentially reducing the economic burden on cucumber farmers.